PRESENTATION OF TOW SABIR ELEMENT RESULTS WITH IRREGULAR SHAPES - T. BELARBI, M.; HAMADI, D. (Courrier du Savoir, 2014)
In 1985, Sabir developed two membrane finite elements having an additional nodal degree of freedom (DRILLING ROTATION). The main objective of this important development is to contribute in modeling the complex structures having only simple geometrical shape. In this paper, a new analytical integration expression is developed in order to model structures have complex geometrical shape. It is of importance to know how these elements will behave when they have irregular shapes.